Identification of Bisphenol A‑Assimilating Microorganisms in Mixed Microbial Communities Using 13C‑DNA Stable Isotope Probing - Sathyamoorthy, Sandeep; Hoar, Catherine; Chandran, Kartik (Environmental science & technology, 2018)
A wide range of trace organic contaminants (TOrCs), including the endocrine-disrupting compound bisphenol A (BPA), are subject to microbial transformations during biological wastewater treatment. However, relatively little is known about the identity of organisms capable of assimilating emerging contaminants. Here, 13C-DNA stable isotope probing (DNA-SIP) was used to investigate biodegradation and assimilation of BPA by mixed microbial communities collected from two full-scale wastewater treatment plant bioreactors in New York City and subsequently enriched under two BPA exposure conditions. The four enrichment modes (two reactors with two initial BPA concentrations) resulted in four distinct communities with different BPA degradation rates. On the basis of DNA-SIP, bacteria related to Sphingobium spp. were dominant in the assimilation of BPA or its metabolites. Variovorax spp. and Pusillimonas spp. also assimilated BPA or its metabolites. Our results highlight that microbial communities originating from wastewater treatment facilities harbor the potential for addressing not only human-derived carbon but also BPA, a complex anthropogenic TOrC. While previous studies focus on microbial biodegradation of BPA, this study uniquely determines the “active” fraction of microorganisms engaged in assimilation of BPA-derived carbon. Ultimately, information on both biodegradation and assimilation can facilitate better design and operation of engineered treatment processes to achieve BPA removal.